2006
DOI: 10.1246/bcsj.79.511
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer Complexes Based on Fine-Controlled Metal Assembling

Abstract: A series of novel dendrimers composed of dendritic phenylazomethines (DPAs) were synthesized with several types of functional cores. The metal assembling to the DPAs is stepwise by the layers, therefore, they can be used as a scaffold for the precise hybridization between metal ions and organic macromolecules. Because of uniform structure of the dendrimer, there is no structural dispersion in the macromolecule-metal hybrid of the DPAs. Also, the number of metal ions loaded in one dendrimer should have no stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 140 publications
(128 reference statements)
2
39
0
Order By: Relevance
“…In our previous study, a DPA with a monosubstituted phenyl group as core also exhibited similar stepwise complexation starting from the core. [16] It is likely that stepwise complexation is a characteristic property of the dendritic phenylazomethine block. Distortion of the inherent property gradient based on the electron density or donor strength should be due to the bent conformation toward the vacant space around the core unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, a DPA with a monosubstituted phenyl group as core also exhibited similar stepwise complexation starting from the core. [16] It is likely that stepwise complexation is a characteristic property of the dendritic phenylazomethine block. Distortion of the inherent property gradient based on the electron density or donor strength should be due to the bent conformation toward the vacant space around the core unit.…”
Section: Discussionmentioning
confidence: 99%
“…This would lead to a system with a polydispersemetal-assembled structure in a monodisperse macromolecular ligand. [16] Since the discovery of stepwise radial complexation in a dendritic polyphenylazomethine (DPA), [17] variations of this molecule were synthesized. [18][19][20][21][22][23][24][25] The DPA family of macromolecular ligands has a unique metal-assembling process in which metal ions bind to the branching monomer units in perfect order from the core to the outside termini.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[118] Recently, Yamamoto and colleagues reported that metalassembling dendritic phenylazomethines could also significantly improve the electron transfer reaction as a protein-like catalyst. [119] Later the same group showed that the lanthanide-ion-assembling dendritic phenylazomethines with a cobalt porphyrin core may also act as an efficient catalyst for the CO 2 electrochemical reduction with a very low potential. [120] Cobalt tetraphenylporphyrin, which is a model of the core unit, is known to catalyse the reduction.…”
Section: Dendrimers In Photodynamic Therapymentioning
confidence: 99%
“…Phenylazomethine dendrimers composed of rigid p-conjugated backbones exhibit exceptionally fine coordination processes, such as step-by-step assembly [29][30][31] , allowing one-atom controlled synthesis of metal clusters 32 . In addition, previous studies have shown that the stable quadrupole character of such dendrimers allows an efficient photoelectric process based on their rectification properties 33 .…”
mentioning
confidence: 99%